Gastroesophageal reflux disease correlation with posterior laryngitis - Dimitrijević Milovan; Beljin Vera; Petrović Vladan; Đukić Vojko (Vojnosanitetski Pregled)
Background/Aim. Over the last years numerous studies have been performed dealing with mutual relations among gastroesophageal reflux disease (GERD) and numerous diseases of the upper airways. The aim of the present study was to establish possible causal relationship between GERD and posterior laryngitis (PL). Methods. The study included 103 patients with gastrointestinal complaints. Diagnostic procedure included a medical history, gastroscopy and laryngeal directoscopy. The obtained data processed using classic methods of the descriptive statistics, as well as Pearson's chi-square test, Student's t test, rank sum test and Fisher's parametric analysis of variance. Results. Out of the total number of 103 examined patients, 33 (32%) were diagnosed with PL, while GERD was diagnosed in five of the examined patients all belonging to the PL group (15% of the patients with PL). In the remaining patients, PL was caused by other factors. All the patients with GERD had PL and globus sensation while 80% of GERD patients had prominent symptom of pain. Conclusion. The results of the study are indicative of the causal relationship between GERD and PL.